Human Mast Cells From Adipose Tissue Target and Induce Apoptosis of Breast Cancer Cells - Plotkin, Jesse D.; Elias, Michael G.; Fereydouni, Mohammad; Daniels-Wells, Tracy R.; Dellinger, Anthony L.; Penichet, Manuel L.; Kepley, Christopher L. (Frontiers in Immunology, 2019)
Mast cells (MC) are important immune sentinels found in most tissue and widely recognized for their role as mediators of Type I hypersensitivity. However, they also secrete anti-cancer mediators such as tumor necrosis factor alpha (TNF-α) and granulocyte-macrophage colony-stimulating factor (GM-CSF). The purpose of this study was to investigate adipose tissue as a new source of MC in quantities that could be used to study MC biology focusing on their ability to bind to and kill breast cancer cells. We tested several cell culture media previously demonstrated to induce MC differentiation. We report here the generation of functional human MC from adipose tissue. The adipose-derived mast cells (ADMC) are phenotypically and functionally similar to connective tissue expressing tryptase, chymase, c-kit, and FcεRI and capable of degranulating after cross-linking of FcεRI. The ADMC, sensitized with anti-HER2/neu IgE antibodies with human constant regions (trastuzumab IgE and/or C6MH3-B1 IgE), bound to and released MC mediators when incubated with HER2/neu-positive human breast cancer cells (SK-BR-3 and BT-474). Importantly, the HER2/neu IgE-sensitized ADMC induced breast cancer cell (SK-BR-3) death through apoptosis. Breast cancer cell apoptosis was observed after the addition of cell-free supernatants containing mediators released from FcεRI-challenged ADMC. Apoptosis was significantly reduced when TNF-α blocking antibodies were added to the media. Adipose tissue represents a source MC that could be used for multiple research purposes and potentially as a cell-mediated cancer immunotherapy through the expansion of autologous (or allogeneic) MC that can be targeted to tumors through IgE antibodies recognizing tumor specific antigens.